Singapore's success as broadcast hub : the picture ahead. - Wee, Adrian Thiam Hock. (2009)
A wave of technology, privatisation efforts and the intention to diversify its economy has led Singapore to branch out into the broadcast industry and strive to be regional broadcast hub. The island ambitious endeavor can presently be witnessed in increased programming choices for the Singapore audience as well as regional viewers, leading to a rise in the number of broadcasters, both local and foreign, to cater to the needs of the Asian populace. To cope with this new reality, a revision, adaptation and/or modification to Singapore's broadcast regulatory system has been put in place.